Wealth inequality in Sweden: What can we learn from capitalized income tax data? - Jacob Lundberg; Daniel Waldenström (Research Institute of Industrial Economics (IFN), 2016)
This paper presents new estimates of wealth inequality in Sweden during 2000-2012, linking wealth register data up to 2007 and individually capitalized wealth based on income and property tax registers for the period thereafter when a repeal of the wealth tax stopped the collection of individual wealth statistics. We find that wealth inequality increased after 2007 and that more unequal bank holdings and apartment ownership appear to be important drivers. We also evaluate the performance of the capitalization method by contrasting its estimates and their dispersion with observed stocks in register data up to 2007. The goodness-of-fit varies tremendously across assets and we conclude that although capitalized wealth estimates may well approximate overall inequality levels and trends, they are highly sensitive to assumptions and the quality of the underlying data sources.
Keywords: D31; H2; N32; 330; Wealth distribution; Capitalization method; Investment income method; Gini co-efficient; Top wealth shares; Great Recession